Flood Prevention and Public Policies:: The Case of Ituporanga ”“ Santa Catarina, Brazil - Mendonça de Moura, João Marcos Bosi; Vieira, Rafaela; Bohn, Noemia (Sustainability in Debate, 2015)
Departing from an analysis of the Brazilian national policies for water resources management, dams safety, and protection and civil defense, this article studies the decision-making process and actions taken to expand the Flood Prevention South Dam (Barragem Sul de Contenção de Cheias, in Portuguese) in the Itajai do Sul river, in Ituporanga-SC. The South Dam is one of the three largest flood prevention dams located in the hydrographic basin of the Itajai River. For the purposes of this article, a critical analysis of bibliographical, documentary and scientific sources was performed. Results show that the natural disasters occurred in 2008 and 2011 in the study region have forced a Governmental response. However, the official decision to expand the South Dam was taken without the necessary coordination among different national policies for water resources management, dams safety, and protection and civil defense”.